Optimization of process parameters for foam mat drying of black rice bran anthocyanin and comparison with spray- and freeze-dried powders - Nattapong Kanha (2020)
© 2020 Taylor & Francis Group, LLC. The foaming conditions and air-drying temperature for producing instant powder from black rice bran anthocyanin extracts were studied. The conditions required for forming a foam to possess the maximum overrun, foam density, and foam stability, which contributed to boost the efficiency of drying foams using a hot-air dryer, were optimized using response surface methodology (RSM). Two independent variables were studied: the foaming agent concentrations (0.02–0.10%, w/w) and the whipping times (7.93–22.1 min). The optimal foaming conditions from RSM were 0.06% (w/w) foaming agent and 16.1 min whipping time, providing foams with the highest overrun (218%), foam density (0.31 g/mL), and foam stability (79.3%). The foams were dried at different temperatures (60, 70, and 80 °C). The best qualities of foam mat-dried powders were observed at 80 °C. Compared to spray- and freeze-dried anthocyanin powders, the total anthocyanin content and encapsulation efficiency of the foam mat-dried powders were comparable and higher to those of the spray- and freeze-dried powders, respectively. However, the solubility and dispersibility of the foam mat-dried powders were lower. The morphology of the foam mat-dried powder showed a smooth, flat shape, with a larger size than the spray- and freeze-dried powders.